In silico identification of promising PD-L1 inhibitors from selected indian medicinal plants for treatment of triple negative breast cancer - Sk. Faisal Ahmed; Md. Shohel Hossain; Amalesh Mondal; Musab Shahariar; Shormila Akter Sumya; Nahid Sultan Rizu; Lamia Hasan Joarder Barsha (PLoS ONE, 2025)
Triple-negative breast cancer (TNBC) is the most aggressive among the breast cancer subtypes and poses unique therapeutic challenges due to its distinct characteristics like lack of specific therapeutic targets. TNBC demonstrates poor survival rate enhanced immunogenic characteristics and a more favorable tumor microenvironment than other breast cancer variants. Also, TNBC patients show elevated levels of programmed death ligand-1 (PD-L1) expression in contrast to non-TNBC patients. Binding of PD-L1 with PD-1 produces an inhibitory signal, resulting in suppression of T-cell. Therapeutic approaches utilizing immunotherapies against PD-L1 exhibit promising outcomes in the treatment of TNBC. Limitations like suboptimal efficacy, inadequate oral bioavailability, and associated immune-related adverse effects of antibody-mediated anti PD-1/PD-L1 therapies have necessitated the exploration of alternative therapeutic approaches. Thus, small molecules become an alternate option for PD-1/PD-L1 inhibition. In the present study, we have used virtual screening to identify potential phytochemicals from selected Indian medicinal plants as PD-L1 inhibitors. A total of 953 phytochemicals derived from eleven selected medicinal plants were initially screened through molecular docking using the PyRx tool. Among the 953 identified phytochemicals, the top 20 compounds exhibiting the highest binding affinities in docking study were selected for further analysis. Following comprehensive ADMET analyses, 2 compounds were ultimately identified as suitable candidates for a molecular dynamics (MD) simulation study. The study identified 4-hydroxychalcone and flavylium from Glycyrrhiza glabra and Catharanthus roseus, respectively as potential PD-L1 inhibitors with enhanced stability relative to the reference molecule. Both compounds also showed enhanced gastrointestinal absorption with no predicted cytotoxic and immunotoxic effects. Consequently, these compounds present promising candidates for novel PD-L1 inhibitor development in TNBC therapy. Further experimental investigations are necessary to facilitate their clinical translation.